2022
DOI: 10.3390/jpm12030429
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in a Familial Hypercholesterolemia Population from North-Eastern Europe

Abstract: (1) Background: Familial hypercholesterolemia (FH) is one of the most prevalent inherited metabolic disorders. The purpose of the study was to investigate the role in cardiovascular disease (CVD) of PAI-1, ACE, ApoB-100, MTHFR A1298C, and C677T. (2) Methods: From a group of 1499 patients, we included 52 patients diagnosed with FH phenotype and 17 patients in a control group. (3) Results: Most of the FH patients had multiple comorbidities compared to the control group, such as atherosclerosis (48.1% vs. 17.6%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…There is much evidence proving the existence of an impact of various genetic parameters on the disease phenotype and CVD risk in the FH population. This applies to genetic variants and SNPs in various genes, including those controlling LDL metabolism, oxidative stress, lipoprotein metabolism, renin angiotensin aldosterone system, and other processes [ 16 ]. Khera et al have found that carriers of an identified FH-causing mutation who suffer from severe hypercholesterolemia had an enhanced CVD risk in comparison to severe hypercholesterolemia patients who did not carry the identified mutation.…”
Section: Genetic Variables In CV Risk In Fh Populationmentioning
confidence: 99%
“…There is much evidence proving the existence of an impact of various genetic parameters on the disease phenotype and CVD risk in the FH population. This applies to genetic variants and SNPs in various genes, including those controlling LDL metabolism, oxidative stress, lipoprotein metabolism, renin angiotensin aldosterone system, and other processes [ 16 ]. Khera et al have found that carriers of an identified FH-causing mutation who suffer from severe hypercholesterolemia had an enhanced CVD risk in comparison to severe hypercholesterolemia patients who did not carry the identified mutation.…”
Section: Genetic Variables In CV Risk In Fh Populationmentioning
confidence: 99%